A systematic review summarizing the effect of health care provider-delivered physical activity interventions on physical activity behaviour in cancer survivors. Issue 7 (July 2020) - Brunet, Jennifer; Wurz, Amanda; Nader, Patrick Abi; Bélanger, Mathieu
Highlights: Health care provider-delivered interventions may enhance physical activity (PA). Effects may depend on whether additional techniques and/or resources to support PA behaviour change are provided. More high-quality research is needed. Abstract: Objective: To synthesize knowledge regarding the effect of health care provider-delivered physical activity interventions on cancer survivors' physical activity behaviour. Methods: Ten electronic databases were searched for articles reporting on the effect of health care provider-delivered physical activity interventions on cancer survivors' physical activity behaviour. Articles were included if they met the following criteria: English-language, participants were adult cancer survivors, the effect of health care provider-delivered physical activity interventions on physical activity behaviour was assessed, and physical activity behaviour was measured at least twice. Data were extracted and summarized descriptively. Results: Seventeen articles representing 11 studies met inclusion criteria. Two studies reported within-person increases in physical activity behaviour and one reported decreases. Nine studies reported between-group differences in physical activity behaviour favouring the intervention group. Conclusions: Health care provider-delivered physical activity interventions may increase cancer survivors' physical activity behaviour. However, increases may depend on administering additional behaviour change techniques and resources. Given the limited number of studies, degree of heterogeneity, and high level of bias observed, more research is needed to ascertain the effect of health care provider-delivered interventions on cancer survivors' physical activity behaviour and to compare different interventions.